Experimental Study of Railway Trackbed Pressure Distribution Under Dynamic Loading - Mykola Sysyn; Vitalii Kovalchuk; Olga Nabochenko; Yuri Kovalchuk; Oleg Voznyak (The Baltic Journal of Road and Bridge Engineering, 2019)
Reliable and durable operation of the railway track under the dynamic load of the rolling stock depends considerably on the ability of the ballast layer to get the load from the sleepers and distribute it to the subgrade. In this paper, the experimental study of the distribution properties of the ballast layer under the impact of dynamic loading depending on the density of the ballast layer is carried out. The ballast behaviour during load cycles is estimated by pressure measurements at the ballast prism base along the axis of a sleeper with simultaneous video observation of the ballast particles movement through transparent sidewalls of the box with crushed stone. Measurements of pressure distribution are carried out with the developed microcontroller system of measurements and developed load cells. The system allows performing multi-point measurements of stress in combination with measurements of acceleration and photogrammetry. The results of measurements showed a significant effect of the ballast layer consolidation on the distribution of stresses under the sleeper. The performed research opens up opportunities for practical improvement of the existing types of track structures and the technology of the ballast layer tamping in terms to provide the optimal conditions for the ballast layer operation.